Serious games as catalyst for intercultural literacy development? : a case study of Immigropoly - Aalto, Johannes (2017)
This thesis inquires into whether a specific online game could be used as a catalyst for intercultural literacy development. The case study focused on Immigropoly, a game aimed at introducing the hardships of immigrants to society at large in Europe by putting players in control of a fictional immigrant character and tasking them with getting that character safely to Europe.